2018
DOI: 10.18203/2320-6012.ijrms20184049
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of extra pulmonary tuberculosis among urban population with special reference to CBNAAT as a diagnostic tool: a retrospective study at a tertiary care hospital of Odisha, India

Abstract: Background: Diagnosis of Extra-pulmonary TB (EPTB) is a challenge. Authors wanted to assess the sites of extra-pulmonary involvement during 2013-2017 in a tertiary care hospital cum medical college. Authors also wanted to evaluate the role of Cartridge Based Nucleic Acid Amplification Test (CBNAAT) in diagnosis of EPTB and compare its efficacy with AFB Culture.Methods: Total 470 EPTB cases diagnosed between 2013 and 2017 from 840 TB treatment records maintained in designated microscopy centre. Specific samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…EPTB was more witnessed in male (54.6%) than female (45.4%). 25 Similar observations were made in the study by Ramaprakash et al, who documented 51.52% males and Mavila R et al, who reported 112 (59.9%) male as sufferers of extra-pulmonary TB. 26,27 CBNAAT results of EPTB specimen revealed higher diagnostic yield from lymph node aspirate and pus compared to no detection from pleural fluid, CSF and peritoneal fluids.…”
Section: Resultssupporting
confidence: 82%
“…EPTB was more witnessed in male (54.6%) than female (45.4%). 25 Similar observations were made in the study by Ramaprakash et al, who documented 51.52% males and Mavila R et al, who reported 112 (59.9%) male as sufferers of extra-pulmonary TB. 26,27 CBNAAT results of EPTB specimen revealed higher diagnostic yield from lymph node aspirate and pus compared to no detection from pleural fluid, CSF and peritoneal fluids.…”
Section: Resultssupporting
confidence: 82%